PERILAKU MAKAN MURID SEKOLAH DASAR PENERIMA PMT-AS DI DESA CIHEULEUT DAN PASIR GAOK KABUPATEN BOGOR - Hermina Hermina; Tjetjep S. Hidayat; Nurfi Afriansyah; Salimar Salimar; Djoko Susanto (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2000)
FOOD CONSUMPTION BEHAVIOR OF ELEMENTARY SCHOOL PUPILS PARTICIPATING IN "PMT-AS" PROGRAM AT THE CIHEULEUT AND PASIR GAOK VILLAGE DISTRICT OF BOGOR.Objective: To collect informations regarding actual food consumption behaviour of the pupils, i.e. to develop right message to improve food consumption and nutrition status of the pupils.Results: Most of the pupils have not been applying good and acceptable food consumption behavior, i.e. quantitatively and qualitatively as well; their dietary food consumption patterns relatively monotoneous, vegetables are consumted very limited and also protein sources are less varieties. Snack foods which are usually consumed at school are less varieties and relatively unsafe.Conclusions: There are important messages developed to improve food consumption and nutrition status of the pupils, i.e. eat breakfast before go to school, have complete meal 2-3 times a day and consumed vegetables every day.Key Words: food consumption behavior, school suplementary feeding program (PMT-AS), nutrition education, elementary school pupils